Identification and Diversity of Killer Cell Ig-Like Receptors in Aotus vociferans, a New World Monkey (2013)
Previous BAC clone analysis of the Platyrrhini owl monkey KIRs have shown an unusual genetic structure in some loci. Therefore, cDNAs encoding KIR molecules from eleven Aotus vociferans monkeys were characterized here; tenputative KIR loci were found, some of which encoded atypical proteins such as KIR4DL and transcripts predicted to encode a D0+D1 configuration (AOTVOKIR2DL1*01v1) which appear to be unique in the Aotus genus. Furthermore, alternative splicing was found as a likely mechanism for producing activator receptors in A. vociferans species. KIR proteins from New World monkeys may be split into three new lineages according to domain by domain phylogenetic analysis. Although the A. vociferans KIR family displayed a high divergence among paralogous genes, individual loci were limited in their genetic polymorphism. Selection analysis showed that both constrained and rapid evolution may operate within the AvKIR family. The frequent alternative splicing (as a likely mechanism generating activator receptors), the presence of KIR4DL and KIR2DL1 (D0+D1) molecules and other data reported here suggest that the KIR family in Aotus has had a rapid evolution, independent from its Catarrhini counterparts.from its Catarrhini counterparts.